Hydrothermal synthesis of pure Talc, Mn and Ni-Doped Talc and their impact on stoneware tiles sintering - Andrea Bloise; Francesco Parisi; Mauro Francesco La Russa; Nicolas Godbert; Iolinda Aiello; Eugenia Giorno; Alessandro Croce; Sara Filicetti; Giovanni Vespasiano; Ilaria Fuoco; Carmine Apollaro (Applied Clay Science, 2026)

Microplastic quantification in Sabellaria reefs: a validated protocol for extraction from biogenic agglutinated matrices - Giusto Lo Bue; Rosa Maria Festa; Maya Musa; Maria Pia Riccardi; Alessandro Croce; Agnese Marchini; Nicoletta Mancin (Environmental Science and Pollution Research, 2026)
Microplastic pollution affects all marine ecosystems, particularly coastal areas inhabited by sedentary reef-building organisms that rely on sand grains to build arenaceous reefs (e.g., Sabellariid polychaetes). These agglutinated reefs passively trap microplastics, thus increasing the potential risk to benthic organisms that live on and within the reef. An accurate quantitative assessment of microplastics accumulated within these arenaceous reefs is currently hindered by a lack of standardized methodologies. This study addresses this gap by developing and validating a reliable and reproducible protocol specifically designed to extract and quantify microplastics cemented within bioconstructed agglutinated matrices. The proposed protocol evaluated digestion procedures aimed at the release of microplastics from agglutinated matrices. The subsequent density extraction procedure was validated via a spiking experiment using both bioconstruction and sediment samples spiked with known quantities of polyethylene terephthalate, polypropylene, and polyvinyl chloride. Scanning electron microscopy and µ-Raman spectroscopy confirmed that the adopted digestion procedures did not alter the plastic polymers. Results also showed that the NaI solution yielded a significantly higher microplastic recovery than NaCl. Notably, microplastic recovery using NaCl was influenced by the initial sample weight, suggesting possible matrix interference at higher sample weights. Our multistep approach provides a validated, cost-effective, and reproducible protocol that improves microplastic quantification in agglutinated matrices. By employing common laboratory equipment and specific procedures, this methodology represents a significant step towards standardizing microplastic pollution monitoring in coastal bioengineered habitats. Highlights • A step-by-step protocol for MP density extraction from biogenic agglutinated matrices was validated. • Agglutinated matrices require disaggregation to release MP, ensuring a correct density extraction. • Preliminary drying and disaggregation procedures do not alter the chemical integrity of MP. • NaI solution is significantly more efficient than NaCl for MP extraction. • Substrate type (sediment vs Sabellariid bioconstruction) had no influence on density extraction efficiency.

Geological and mineralogical characterization of fibrous tremolite from Iacolinei quarry (Basilicata, Italy) - Alessandro Pacella; Paolo Ballirano; Maria Cristina Di Carlo; Alessandra Altieri; Marco Paccapelo; Henrik Skogby; Antonella Campopiano; Maria Rosaria Bruno; Alessandro Croce; Costanza Piersante; Carmine Apollaro; Giacomo Malvasi; et al. (Environmental Geochemistry and Health, 2024)

First attempt to quantify microplastics in Mediterranean Sabellaria spinulosa (Annelida, Polychaeta) bioconstructions - Giusto Lo Bue; Agnese Marchini; Maya Musa; Alessandro Croce; Giorgio Gatti; Maria Pia Riccardi; Stefania Lisco; Nicoletta Mancin (Marine Pollution Bulletin, 2023)

From Stromboli ashes to corrensite by hydrothermal synthesis: Hydrogeological inputs into Mars history - Chiara Benedetta Cannata; Nicolas Godbert; Rosanna De Rosa; Iolinda Aiello; Eugenia Giorno; Alessandro Croce; Andrea Bloise (Applied Clay Science, 2023)

Prognostic Value of EEG Microstates in Acute Stroke - Filippo Zappasodi; Pierpaolo Croce; Alessandro Giordani; Giovanni Assenza; Nadia M. Giannantoni; Paolo Profice; Giuseppe Granata; Paolo M. Rossini; Franca Tecchio (Brain Topography, 2017)